قيمة الحرية في الفكر الغربي الحديث -الشذوذ الجنسي نموذجا- - بن عطية منى; شبايكي الجمعي (University of Eloued جامعة الوادي, 2023)
ملخص: شهد الاهتمام بقيمة الحريّة تطورا كبيرا في العصر الحديث عاكسا المنزلة التي أصبح يحتلها الفرد في التمتع بحقه داخل الدولة والمجتمع، ما أتاح لبعض الفئات المجتمعية كفئة الشواذّ في المجتمع الغربي المطالبة بحقّها في التمتع بحرية التعبير عن أفكارها وممارسة قناعاتها،إلا أن هناك قيودا ومعايير مختلفة في النظر لقيمة الحريّة تختلف من بلد لآخر، ومن منظومة فكريّة لأخرى، فهناك من يدعو إلى إطلاقها بدون قيود، وهناك من يدعو إلى التعقّل في تمثلها وإلى الانضباط بالآداب والقيم الدّينية لتثمر حقا تلك المفاهيم النبيلة المرتبطة بها. إن الاختلاف في النظر لقيمة الحرية يرجع إلى اختلاف المقومات الفكرية والرصيد التاريخي الثقافي والمعرفي لكل حضارة ولكل دين، لذلك عندما يريد المرء دراسة الحرية في مجتمع ما يجب عليه لتطرّق للخلفيّة التي شكّلتها ليتمكن من تحليلها ونقدها. وقد جاءت هذه الدراسة لتلقي الضوء على قيمة الحرية في حادثة رفض المسلم السنغالي إدريسا غاي–لاعب كرة القدم- ارتداء قميص يحمل ألوان علم الشذوذ الجنسي، وقد توصلت إلى أن الحريات العامة التي ينادي بها الغرب لم تكن في يوم من الأيام هدفا بحد ذاتها، بل عرضا لتنامي إرادة القوة في أوربا، والقبول بالحوار يعتمد على تحقيق المصالح الخاصّة بهم. كما أن للشذوذ الجنسي فلسفة تاريخيّة عند من يدعون إليه، فهو ليس مجرّد تحدّ للمجتمع الحديث وأخلاقه التقليدية. abstact: Interest in the value of freedom has seen a great development in modern times. This has enabled certain social groups, such as homosexuals in Western society, to claim their right to freedom of expression and the freedom to practice their beliefs. However, there are different restrictions and criteria for assessing the value freedom which differ from one country to another, and from one intellectual system to another. The difference in the consideration of the value of freedom is due to the different intellectual components and the historical, cultural and cognitive stock of each civilization and each religion. Thus, when we want to study freedom in a society, we must look at the context that has formed. so that we can then analyze and criticize it. For this reason, this study has come to illuminate the value of freedom in the incident of the Senegalese Muslim Idrissa Guy - the football player - refusing to wear a shirt with the colors of the flag of homosexuality ,and it has concluded that the civil liberties that the West demands today have never been an end in themselves, but rather a symptom of the growth of the will to power in Europe, and that the acceptance of dialogue depends for the pursuit of their own interests. As well as homosexuality has a historical philosophy for those who defend it, because it is not only a challenge to modern society and its traditional morality.
Keywords: القيم; الحرية; حرية الشذوذ الجنسي; الحرية في الإسلام; الفكر الغربي الحديث; Values; freedom; homosexuality; freedom in Islam; modern Western thought